(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Over the years, entrepreneurship has become ubiquitous in the business ecosystem. Perhaps it contributes positively to national economies and has been widely considered among the primary engines of economic growth and job creation. Thus, understanding the possible determinants of the variation in entrepreneurial aspiration among the youth is vital for helping the government and policymakers adopt adequate measures to support the creation and development of new ventures. In recent years, the turbulent economic realities in Nigeria, dominated by financial crises, have affected entrepreneurship development. Thus, this paper investigated the effect of economic stress on entrepreneurial aspiration among prospective entrepreneurs in River State, Nigeria. A convenience sample of three hundred and twenty-two undergraduates pooled from five tertiary institutions in the River State participated in the study. The study results underscored rising inflation in the country as a significant macroeconomic determinant of entrepreneurial aspiration among the youth